PENDAMPINGAN MANAJEMEN USAHA BATIK TANULOMBO DAN TAS ANYAMAN MELALUI KEGIATAN PPK ORMAWA - Muhammad Arrasyid, Faiz; Aryati, Deni; Nur Khofifah, Leni; Tafrichan, Ahmad; Rifa’i, Rohman; Nurul Azizah, Arifah; Sania Masruroh, Wulan; Jumini, Sri; Putri hanifah, Desty; Nulngafan, Nulngafan; Hermanto, Heri (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
The development of the batik and woven bag business world is increasingly demanding that all business actors be more mature in managing their businesses. Business management plays an important role in the success of increasing income and business sustainability. Batik Talunombo is a pioneer of batik motifs Carica, Purwaceng, and Candi Dieng, which uphold local wisdom. While woven jali bags are a new business with modern bags that use synthetic and economical materials. However, the fact is that the business being run is not well organized. The ability of planning, marketing, HR management, and product innovation is not yet optimal. The impact is that the product is not sold every day. Seeing this, the Implementation Team, through the PPK Ormawa UNSIQ community service activities, carried out business management mentoring activities in Talunombo village, Sapuran District. This community service was carried out by 18 woven jali bags and batik Carica business actors. During the mentoring, the positive and enthusiastic response of the participants who participated reached a 100% attendance percentage. The increase in participant abilities during the training was proven by the ability to work on pretest and posttest questions given in the moderate category. Meanwhile, for its derivative products, innovations have been created for derivative products of batik carica lestari and celosia into the Az Zahra batik carica cluster. Its marketing through Instagram has increased. The impact of this activity is that training participants understand the material on planning, organizing, actualizing, and controlling businesses well, carrying out product innovation, and evaluating products periodically so that the businesses they run can grow, compete, and be sustainable.